IMPLEMENTASI TRADISI BAADAT PADA RITUAL KEMATIAN MASYARAKAT HINDU KAHARINGAN DI KABUPATEN LAMANDAU - I Gusti Agung Dharmawan; Derson Derson (Widya Sandhi Jurnal Kajian Agama Sosial dan Budaya, 2022)
Culture is the whole complex which includes knowledge and belief, art, morals, law, customs, and habits acquired by humans as members of society. The Hindu Kaharingan community in Lamandau Regency has various kinds of religious rituals, including birth, marriage, and death. One thing that is very unique and there is a phenomenon to be studied in this research is that there is a tradition in the ritual of death called the Baadat tradition which is a tradition that can only be done by one family group who is Hindu Kaharingan only, and Baadat is only done when a family member died. This tradition is very unique in that it is a cultural hasanah or heritage from our ancestors which has a very high philosophical meaning when compared to other religious ritual traditions. Therefore, traditions like this must be preserved and maintained in their integrity even though they face various challenges and obstacles as a result of the impact of the influence on the entry of modern cultures that can change from the actual cultural order, especially in the Baadat tradition of death rituals.